Keep running - Fanning, Tony; Fanning, Robbie (New York : Sovereign Books, 1978)
It's a lot harder to keep running than it is to start running. Ten million runners are on the road, but we know that next month it won't be the same 10 million. Like its cousins, the I'm-Quitting-Smoking Club and the Dieters' Club, the Runners' Club has an enormous turnover.
1. Basics -- 2. Where are You Now -- 3. Outfitting Yourself -- 4. Re Starting -- 5. Your First Running Schedule -- 6. The Run Itself -- 7. How Much Should I Run? -- 8. The Runner's Body -- 9. The Runner's Mind -- 10. A Dictionary of Impediments -- 11. More Than The Missionary Position -- 12. Man and Women -- 13. Past It On.
Includes bibliographical references and index.
Keywords: RUNNING